Biofuels in Southern Africa: Political economy, trade, and policy environment - Taku Fundira; Giles Henley (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Expansion of biofuels production and consumption at the regional and national levels relies on both supportive energy prices and policy interventions. Despite enthusiasm for policy interventions to stimulate biofuel production in Southern African countries in the mid-2000s, the years since have seen a decline in interest due to concerns over environmental and social externalities, and the costs associated with subsidies. This paper reviews the state of the policy, regulation, and narratives around opportunities and challenges for biofuels in each country to assess broader challenges associated with expanding biofuels production and consumption at a regional level.
Keywords: 330; biofuels; Southern Africa; policy; Zambia; Mozambique; South Africa